A year at the improv: the evolution of teacher and student identity in an elementary school makerspace. Issue 1 (2nd January 2023) - Becker, Sandra; Jacobsen, Michele
ABSTRACT: This article presents findings from a design-based research study that investigated curriculum implementation in a makerspace with a grade six teacher and her class over the course of one year. In comparing the figured worlds of classroom and makerspace, the authors explore through the examples of three students and the teacher how they each adopted personal improvisations from the makerspace into the culture of the classroom, leading to developments in agency and identity on the part of all. In particular, by engaging in collaborative design-based research, the teacher was able to embrace the iterative, collaborative, risk-taking nature of maker culture, which led her to rethink and transform her teaching practice. Findings suggest that the makerspace serves as a specialized learning environment in which teachers can prototype inquiry-based approaches to curricular learning.